The adoption of blockchain-supply chain framework among halal food producers / Siti Fairuza Hassam and Purnomo M Antara - Hassam, Siti Fairuza; M Antara, Purnomo (Universiti Teknologi MARA, Kedah, 2022)
The halal food industry has developed into a significant global food industry. This industry is no longer a new economic growth sector but a competitive economy. Moreover, Halal is now becoming an essential source of the economy. The growth of the Halal sector is expected to reach USD5.0 trillion in 2030 (HDC, 2020). In Malaysia, the Halal market growth is expected to reach USD113.2 billion in 2030 (HDC, 2020). This development of this Halal economy was motivated by the Muslims that assert their values and a large Muslim population in Malaysia that reached 20 million (DOSM, 2021). Engaging in what is Halal (permitted) and avoiding that which is Haram (prohibited) is one of the practices of Islam, a Muslim must only choose Halal food to be consumed. However, this situation leads to more complex and become a major challenge to secure a consistent process related to halal food supply chain. Blockchain technology seems to give the halal food supply chain a new era (Ali et al., 2021). There is a need for more exploration and investigation on the blockchain technology implementation into the industry that integrated with the Halal food supply chain environment. Therefore, this paper aims to discuss the necessity of blockchain technology in the Halal food supply chain industry especially the Halal food producer. Besides, this paper also trying to conceptualize and identify the impact of environment, innovation, individual, technology, and organization on intention to adopt blockchain in Halal food supply chain among Halal food producers. This framework of Blockchain-Supply chain is used to provides important insights into the variables influencing the decision of Halal food manufacturers to use blockchain technology in their supply chain. Stuart Haber and W. Scott Stornetta first introduced the blockchain concept in 1991 (Narayanan, et al., 2016). Blockchain is a peer-to-peer transaction network that uses distributed ledger technology (DLT). This technology can determine the guidelines for how information is updated and is used to store any kind of data. As computer-based nodes in the blockchain technology, various entities participate in the transaction. In addition to having a copy of the distributed ledger, each participating node will also be further connected to other nodes in the distributed peer-to-peer networks. Blocks (commercial transactions) will be stored in the distributed ledgers in the main chain, and the distributed ledger technology (DLT) will manage the ledgers of each node of the chain. The block is chained and linked to the previous block in the main chain using a hash number to grow the ledger (Derks et al., 2018). A typical supply chain usually involves multiple partners, including manufacturing plants, suppliers, transporters, distribution centers, and intermediaries. All these parties usually participate in information, material, and cash flow (Bhardwaj et al., 2021). On the other hand, the global supply chains involve import, export, forwarding, and delivery in international trading, increasing supply chain complexity. Through the numerous enhancing activities enabled, such as recording, tracking, and accurately exchanging information, blockchain integration is projected to improve the overall performance and dependability of the Halal food supply chain. The real-time digital ledger of transactions and the movement for all stakeholders in their supply chain network can improve the Halal food supply chain.